AN APPLICATION OF FUZZY GENETIC ALGORITHM FOR ACTIVE QUEUE MANAGEMENT - AQM - Huy, Nguyễn Phương; Hoang, Lê; Dũng, Lê Bá (Vietnam Journal of Science and Technology, 2012)
SUMMARY Currently, all types of information services tend to integrate the Internet. To transport large amounts of data and better support for new Internetapplications such as voice over IP and video on demand need to design algorithms for congestion control and efficient management of the queue. In this paper, we introduce a queue management algorithm - GA-Fuzzy-AQM, a fuzzy improvement for the well-known RED (Random Early Detection) AQM algorithm. Simulation results show that queue management algorithm GA-Fuzzy-AQM proposed has better performace than the traditional RED mechanism.